Migrant women and LMD. Towards the generization of communication with foreign population - Valero Garcés, Carmen (Estudios de Traducción, 2023)
Gender issues have not always been taken into account in when analysing the migration phenomenon, nor has the role of the migrant woman as a link in communication with the migrant population that does not share the same language and culture been sufficiently valued. The main objective of this article is to offer a critical approach to the generization (Gregory Gil 2016) of communication with foreign populations. To this end, firstly, and by way of introduction, the study is contextualised by drawing attention to language as a fundamental right and the need, challenges and solutions posed by its fulfilment in today's society. Secondly, it focuses on the role of migrant women in today's society. Thirdly, the concept of generization of communication with a foreign population is explored and illustrated through the testimony of migrant women speakers of lesser-used languages (LMD). The main conclusion derived from this exploratory study - with its limitations - indicates that migrant women through mediation, translation and interpreting are active agents and necessary architects of communication with foreign populations.
Keywords: Migration; migrant women; gender; gender mainstreaming; lesser-used languages; communication; mediation; interpretation; translation